2012
DOI: 10.1371/journal.pone.0032727
|View full text |Cite
|
Sign up to set email alerts
|

An Observational Cohort Comparison of Facilitators of Retention in Care and Adherence to Anti-Eetroviral Therapy at an HIV Treatment Center in Kenya

Abstract: BackgroundMost HIV treatment programs in resource-limited settings utilize multiple facilitators of adherence and retention in care but there is little data on the efficacy of these methods. We performed an observational cohort analysis of a treatment program in Kenya to assess which program components promote adherence and retention in HIV care in East Africa.MethodsPatients initiating ART at A.I.C. Kijabe Hospital were prospectively enrolled in an observational study. Kijabe has an intensive program to promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 28 publications
1
35
2
Order By: Relevance
“…We excluded 17 studies [44], three studies were excluded due to non-inclusion of community-based data [5557] while seven studies were excluded because the studies were non-comparative [19, 5862]. One study was also excluded because only baseline data were reported [63] while four did not show outcome data for different arms of the studies [17, 6466]. …”
Section: Resultsmentioning
confidence: 99%
“…We excluded 17 studies [44], three studies were excluded due to non-inclusion of community-based data [5557] while seven studies were excluded because the studies were non-comparative [19, 5862]. One study was also excluded because only baseline data were reported [63] while four did not show outcome data for different arms of the studies [17, 6466]. …”
Section: Resultsmentioning
confidence: 99%
“…Six articles reported on multiple outcomes while 14 addressed one outcome of interest (Table 1). The majority of studies were conducted in sub-Saharan Africa: South Africa, n=7 15, 18, 22, 26, 32, 35, 36 ; Kenya, n=2 23, 30 ; Mozambique, n=2 17, 17 ; and one each from Nigeria 25 , Rwanda 24 , Tanzania 21 , Uganda 31 and Zimbabwe. 27 Two studies were conducted in Vietnam 33, 34 ; the remaining two reported multi-country results.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies 15, 18, 21, 2326 reported on the impact of support group interventions on a range of morbidity outcomes (Table 1). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the World Health Organization (WHO) and President's Emergency Plan for AIDS Relief (PEPFAR) propose the engagement of support groups as an intervention to address retention and adherence among PLHIV receiving antiretroviral therapy (ART) [8][9][10]. Many studies have already reported the impact that PLHIV support groups have on increased adherence to ART [11][12][13][14]. More strategically and given the shortage of trained health human resource in many sub-Saharan African countries, support groups can play an increasingly larger role with regard to the bottom lines of improved adherence to treatment and retaining HIV-infected persons in care.…”
Section: From Three Ones To Four Ones -Time For a Review And Updatementioning
confidence: 99%